The Spirit of Enthusiasm: A History of the Catholic Charismatic Renewal, 1967-2000 - Maurer, Susan A. (Hamilton Books, 2010)
In February 1967, a group of Catholic faculty members and students attending a spiritual retreat at Duquesne University experienced what they called a 'baptism in the spirit.' The experience of the 'Duquesne Weekend' spread rapidly to other college campuses in the Midwest and then throughout the United States. The Spirit of Enthusiasm examines the historical development of the American Catholic Charismatic Renewal from the early influences of the Spanish Cursillo movement, through the initial 'baptism in the spirit' event at Duquesne University in 1967, and the Renewal's subsequent development through the end of the 20th century. The influence of the Second Vatican Council on the movement and changes both within the movement itself, as well as in its relationship with the church, are explored. Similarities to, and differences from, the Protestant Pentecostal movement of the 20th century and the nature of Charismatic spirituality are also examined.